A review on genotoxic and mutagenic effects of monoterpenes - Islam, Muhammad (International Journal of Medicine, 2017)
This review sketches genotoxic and mutagenic potentials of monoterpenes, which find outs some important genotoxic, mutagenic as well as non-genotoxic and non-mutagenic monoterpenes. Monoterpenes are the important natural products.